1997
DOI: 10.1051/aas:1997231
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of the observations of the mutual phenomena of the Galilean satellites made in 1991 during the PHEMU91 campaign

Abstract: Abstract. In this paper, all the light-curves obtained during the PHEMU91 campaign of observations of the mutual phenomena of the Galilean satellites are presented. These observations give accurate astrometric positions of major interest for dynamical studies of the motion of the Galilean satellites. The aim of this work is to give observational data directly usable for theoretical studies. We made 374 observations of 111 mutual events from 56 sites. The corresponding data are given in this paper 1 . The accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The characteristics of such phenomena and the results of observations are described in many publications (see e.g. Arlot et al 1982Arlot et al , 1992Arlot et al , 1997Emelianov et al 2000;Arlot et al 2006). Astrometric reduction of these observations was performed by a number of authors (Aksnes & Franklin 1976;Aksnes et al 1984;Vasundhara 1991;Emelianov et al 2000;Vasundhara 2002;Vasundhara et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of such phenomena and the results of observations are described in many publications (see e.g. Arlot et al 1982Arlot et al , 1992Arlot et al , 1997Emelianov et al 2000;Arlot et al 2006). Astrometric reduction of these observations was performed by a number of authors (Aksnes & Franklin 1976;Aksnes et al 1984;Vasundhara 1991;Emelianov et al 2000;Vasundhara 2002;Vasundhara et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the results of the international campaign in 1973 of the mutual events of the Galilean satellites, Aksnes (1976) showed that differences in the observed and predicted mid times and depths of the events can be used to revise the orbital constants of the theory. Subsequent International campaigns and analysis of the observations during the 1979, 1985, 1991, 1997, 2003 and 2009 apparitions have provided an extensive data set of inter satellite astrometric positions (Aksnes et al 1984;GSO 1991;Vasundhara 1991;Arlot et al 1992;Mallama 1992;Vasundhara 1994;Arlot et al 1997;Kaas et al 1999;Vasundhara 2002;Vasundhara et al 2003;Arlot et al 2006Arlot et al , 2009Emelyanov 2009;Dias-Oliveira 2013;Arlot et al 2014). Following the success of the jovian mutual events, the technique has been extended to mutual events of ⋆ E-mail:rvas@iiap.res.in(RV),selva@iiap.res.in(GS), anbu@iiap.res.in (PA) saturnian system in 1995 and 2009 (Thuillot et al 2001;Mallama et al 2009;Arlot et al 2012;Zhang, Liu & Tang 2013), and uranian system in 2007(Asafin et al 2009Christou et al 2009;Arlot et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here we summarize those topics and focus on science themes not previously covered and that can be researched by the overall community of professional astronomers using data from PVOL2. (Arlot et al, 1992(Arlot et al, , 2014. High-resolution observations of Ganymede may become of interest after the launch of the Jupiter ICy moons Explorer (JUICE) mission in 2022 (Grasset et al, 2013).…”
Section: Modern Scientific Cases For the Analysis Of Amateur Datamentioning
confidence: 99%
“…Since then, Mousis et al (2014) -Satellites of the Giant Planets: The database incorporates images of the Galilean satellites of Jupiter and images of satellites mutual phenomena (transits, occultations, eclipses, all of them generally known as Phemus). The scientific use of amateur observations of Jupiter satellites mutual phenomena is well documented (Arlot et al, 1992(Arlot et al, , 2014. High-resolution observations of Ganymede may become of interest after the launch of the Jupiter ICy moons Explorer (JUICE) mission in 2022 (Grasset et al, 2013).…”
Section: Modern Scientific Cases For the Analysis Of Amateur Datamentioning
confidence: 99%